SINTESIS METABOLIT SEKUNDER PADA TUMBUHAN SAMBILOTO (Andrographis paniculata. Ness) DENGAN PERLAKUAN PUPUK DAN INTENSITAS CAHAYA MATAHARI YANG BERBEDA - Nurhayu Malik (BioWallacea : Jurnal Penelitian Biologi (Journal of Biological Research), 2016)
ABSTRACTThis study aims to evaluate the effect of fertilization and different light intensity on secondary metabolite synthesis of bitter plant (Andrographis paniculata Ness) and the ideal harvest age to obtain the highest levels of secondary metabolites. The study was conducted using Completely Randomized Design (CRD) with factorial 3 x 3. The main factor is fertilization treatment which consist of three levels : NPK (Urea 1.2 grams / plant, TSP 2.4 g / plant and KCl 0.6 g / plant), animal manure (1.2 kg / plant) and without fertilization. The second factor is the different light intensity which consist of three levels: full light intensity, half-shade and full shade. For Each treatment combination 3 replicates were used. Measurement of levels of secondary me tabolites by HPTLC method based on the dry weight of 50 mg / plant for each treatment combination. Data were analyzed using the Analysis Of Variance (ANOVA).The results obtained showed that bitter plant response differently to fertilization and different light intensity on secondary metabolite synthesis. Light intensity effected the synthesis of secondary metabolite of bitter plant, if the harvest was conducted at of 1 month after planting, the highest levels found on NPK fertilizer or without fertilizer with light intensity 100%. When the plants were harvested at 2 months after planting There was no effect of light intensity in all treatment combinations.Keywords : Secondary metabolites, fertilizers, light intensity